Effect of Process Parameters in Hot Press Forming Operation to Tensile Strength of Ultra High Strength Steel - Mohd Zairulnizam, Mohd Zawawi; Nik Mohd Hafiz Aiman, Nik Haron (Trans Tech Publications, Switzerland, 2014)
The escalating issues on sustainable environment such as the necessity to reduce CO2 emission and fuel consumption including new regulations to improve the safety of passengers car had brought up the application of new innovative materials and manufacturing process in the automotive industry called hot press forming operation. By using this new technique, the manufacturers can produce more lightweight and high strength car parts such as the B-pillars with tensile strength ranging from 1200MPa to 1600MPa. Hot press forming is done by rapidly heating up Ultra High Strength Steels (UHSS) made of boron steel material in a furnace to austenization temperature of about 950°C for 5 minutes, then transferred it quickly to the hot press die where rapid quenching occurred during the die closed with the aid of cooling channel. This experiment investigates the effects of varying combination of hot press forming parameters to final tensile strength of boron steel and had been carried out without use of cooling channel. The studied parameters are the air cooling time, cooling rate, cooling time in die and stamping pressure. The type of boron steel material with trade name of Usibor® 1500 was used as the test specimens while for punch and die material, High Thermal Conductivity Tool Steel (HTCS-150) made by Rovalma was used. Both are common materials used in the automotive industry for hot press forming operation. A preliminary experiment had been conducted where ten flat tensile strength specimens of Usibor 1500 were heated to the austenization temperature of 950°C and immediately quenched in a tank of water to confirm the material ability to achieve the minimum tensile strength of 1500Mpa. All specimens achieved average tensile strength of 1550Mpa in this most ideal cooling rate condition. In the experimental hot press forming operation, result shows that the flat blank specimens of Usibor 1500 able to obtain ultimate tensile strength of 1400Mpa after quenching in die without use of cooling channels when suitable process parameters were used during. Overall ,faster air cooling time, higher stamping pressure applied to the blank, and longer cooling time in die improve the cooling rate. Highest tensile strength of 1400Mpa was achieved in the experiment when cooling rate was 95°C/s, air cooling time of 3.83s, stamping pressure of 50bar and cooling time in die of 30s.